COVID-19 and Renal Diseases: An Update - Bitencourt, Letícia; Pedrosa, Ana L.; de Brito, Stephanie Bruna Camilo Soares; Fróes, Ana Cláudia Fontoura; de Carvalho, Sarah Tayná; Fonseca, Giulio Gori; Ferreira, Guilherme Costa; Fradico, Pollyanna Faria; Simões e Silva, Ana Cristina (Current Drug Targets, 2021)
Background: It becomes increasingly evident that the SARS-CoV-2 infection is not limited to the respiratory system. In addition to being a target of the virus, the kidney also seems to have a substantial influence on the outcomes of the disease. Methods: Data was obtained by a comprehensive and non-systematic search in the PubMed, Cochrane, Scopus and SciELO databases, using mainly the terms “SARS-CoV-2”, “COVID-19”, “chronic kidney disease”, “renal transplantation”, acute kidney injury” and “renal dysfunction” Discussion: The membrane-bound angiotensin-converting enzyme 2 is the receptor for SARS-CoV- -2, and this interaction may lead to an imbalance of the Renin-Angiotensin System (RAS), associated with worse clinical presentations of COVID-19, including acute pulmonary injury, hyperinflammatory state and hematological alterations. In the framework of renal diseases, the development of acute kidney injury is associated mostly with immune alterations and direct cytopathic lesions by the virus, leading to higher mortality. As for chronic kidney disease, the patients at a non-terminal stage have a worse prognosis, while the hemodialysis patients appear to have mild courses of COVID-19, probably due to lower chances of being affected by the cytokine storm. Furthermore, the current scenario is unfavorable to kidney donation and transplantation. The relationship between COVID-19 and immunosuppression in kidney transplantation recipients has been greatly discussed to determine whether it increases mortality and how it interacts with immunosuppressive medications. Conclusion: The kidney and the RAS exert fundamental roles in the SARS-CoV-2 infection, and more research is required to have a complete understanding of the repercussions caused by COVID-19 in renal diseases.
Keywords: SARS-CoV-2